Reutilização da água de tratamento de efluente na indústria cervejeira por filtração com membrana: uma revisão - Neves, Thiane Lopes das (Brasil, 2021)
The brewing industry generates a high amount of effluents in the stages of the production process, the residues have a significant potential for pollutants. In the beer production process there is a high consumption of water, which arouses the interest of companies to identify opportunities to reduce the use of water in the production process and reuse water after effluent treatment, in order to reduce industrial waste, which has a high rate of contaminants. This work relates bibliographic research and brewing industry effluent treatment, aiming to show that it is possible to reuse the effluent treatment water composed of a UASB reactor associated with a membrane bioreactor (BRM), through estimation of material removal efficiencies organic, having as reference for the reactor UASB + BAS, the efficiency for SST (92%), BOD (89%) and COD (93%) and with BRM, the efficiency for SST (99%), BOD (98%) and COD (99%). As it is possible to reuse water for flushing toilets, washing floors and ornamental purposes, for a more noble application, the effluent needs to undergo sizing and qualitative and quantitative study.